2022
DOI: 10.3233/faia220323
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neural Classification of Darknet Traffic

Abstract: Darknet is an encrypted portion of the internet for users who intend to hide their identity. Darknet’s anonymous nature makes it an effective tool for illegal online activities such as drug trafficking, terrorist activities, and dark marketplaces. Darknet traffic recognition is essential in monitoring and detection of malicious online activities. However, due to the anonymizing strategies used for the darknet to conceal users’ identity, traffic recognition is practically challenging. The state-of-the-art recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Study on obfuscated Tor traffic analysis [1], [2], [3] Non-obfuscated traffic Study on non-obfuscated traffic analysis [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17] Multiple browser classification Study classifying the darknet traffic into multiple browsers [18], [19], [20] Browser settings Classification of the darknet browser through its settings [21], [22], [23], [24], [25] Padded traffic detection Classification of traffic after applying the defense mechanism [6] Traffic classification under adversarial settings Classification of Tor traffic under adversarial settings [1], [26] Application-based…”
Section: Obfuscated Trafficmentioning
confidence: 99%
See 1 more Smart Citation
“…Study on obfuscated Tor traffic analysis [1], [2], [3] Non-obfuscated traffic Study on non-obfuscated traffic analysis [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17] Multiple browser classification Study classifying the darknet traffic into multiple browsers [18], [19], [20] Browser settings Classification of the darknet browser through its settings [21], [22], [23], [24], [25] Padded traffic detection Classification of traffic after applying the defense mechanism [6] Traffic classification under adversarial settings Classification of Tor traffic under adversarial settings [1], [26] Application-based…”
Section: Obfuscated Trafficmentioning
confidence: 99%
“…Alimoradi et al [9] suggested a novel decision support system called a Tor-VPN detector to categorize raw darknet data. The detector uses a deep neural network design with 79 input artificial neurons and six hidden layers to uncover complicated nonlinear relations from raw darknet traffic.…”
Section: Detection Of Non-obfuscated Tor Trafficmentioning
confidence: 99%
“…The global process uses the principles of exploration and exploitation to enhance the algorithm's performance. The global process stops when a predefined number of iterations is reached, and the best solution in the forest is returned [10], [41].…”
Section: Trees Social Relationship Algorithmmentioning
confidence: 99%
“…The main purpose of the machine learning algorithm is to learn correctly and, more importantly, to answer test samples correctly. For this reason, one of the important research fields in data mining is data balancing [3], [4]. Data that does not have an equal value of all classes of instances is called an imbalance.…”
Section: Introductionmentioning
confidence: 99%